Analysis and Experiments of Resonant Coupling Wireless Power Transfer System for Nonuniform Powering of Multiple Sensors - Thuc Phi Duong; Ngoc Hung Phi; Bilal Ahmad; Sasani Jayasekara; Jong-Wook Lee (Sensors)
With a quickly increasing number of Internet of Things (IoT) involving different power levels, wireless power transfer (WPT) systems need the capability to deliver energy to multiple receivers simultaneously. The nonuniform powering of multiple receivers is also necessary, considering the different power levels that IoT sensors demand. This paper investigates asymmetric resonant coupling WPT systems for powering multiple receivers. We propose a simple method for achieving the specified power ratio of the multiple receivers using the equivalent circuit model and reflected impedance technique. The results are generalized for a system with an N number of multiple receivers. Experiments are performed for powering two receivers with power ratios of 1.5 and 2.5, which achieve a power transfer efficiency of 91.7% and 88.6%, respectively. Another experiment performed for powering four receivers, which have power ratios of 1.0, 1.5, 2.0, and 0.75, shows an efficiency of up to 89.9%, which agrees well with the simulation result. Our result shows that the distance between the source loop and the transmitting resonator can be varied to maximize efficiency without altering the power division.